Procedure of Conversion in Village to City and its Results in Talesh Township - mohamad hasan Zia - Tavana; shahram Amir Entekhabi (جغرافیا و توسعه, 2007)
During the recent half-century, one of the hurried urban-bias procedures on spatial and population structure of the country is increasing growth of the numbers of cities through changing of rural centers to small cities. On the other hand, some knowledgeable think that strengthen of urban operations, through changing of rural centers to cities, may cause to better servicing to rural centers. Although modern urban operations and increasing in population in these centers, will be leaded to this matter that in some fertile regions such as those plains beside the Caspian Sea, landscapes of rural centers and agricultural lands applications will be changed. Such a procedure in narrower limits of the Caspian coastal low-lying plains (such as Talesh Township) where population centers have been concentrated, naturally, some more important spatial and economical issues would be resulted. Narrowness and lengthwise shape of Talesh Township have been caused that numerous rural districts markets in linear arrangement have been formed in the nodules in wholesale road and basin of the rivers in the region. These markets are naturally the central location of some villages. Thus, their changing to city will cause not only important social, economical and spatial evolution in those centers, but also will affect their diffusion limits, exclusively. In order to investigation the results of this procedure, at first, through some questionnaires, we studied the effects of changing of rural districts to city in those families that are residing in these locations and also the villages in their diffusion limits, and investigated the attained results from the population, through Spearman method to evaluate the economical and social selected indexes to study the amount of their correlation with some indexes such as the amount of tendency to stay in the place of residence, providing the occupation fields, attraction of unemployed persons, improvement of agricultural status, amount of improvement of the life level and enjoyment of the related services. While, in order to evaluation of the structural and spatial effects of the procedure of changing the villages to cities, some field and deed data  such as plans, statistical data, and information from administrational and local institutes, have been used. The result of the research shows the concentration more than before of population, commercial and servicing activities at narrow bond of the wholesale road that consequently, together with connection to the places of residence around the road, rural concentration is being formed. While, perforated and diffusive structure of limits of new cities are rapidly filled by urban constructions. But through putting into operation of garden-cities model, may cause a compromise between spaces and the urban and rural operations, such a way that among preserving the agricultural lands and natural spaces, diffusive rural residences will be profited from the basic and subordinate urban services and facilities too, and at last they will reach to a structural-operational unity.